2023
DOI: 10.1055/a-2151-2063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Regular Endurance Training Program on Running Economy and Biomechanics in Runners

Sergio Rodriguez-Barbero,
José María González Ravé,
Daniel Juárez Santos-García
et al.

Abstract: A regular endurance training program may elicit different adaptations compared to an isolated training method. In this study, we analyzed the effects of 8 weeks of a regular endurance training program on running economy (RE), particularly neuromuscular and biomechanical parameters, in runners of different athletic abilities. Twenty-four male runners were divided into two groups: well-trained (n=12) and recre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Among the spatiotemporal metrics, only increases in contact time were significantly associated with improvements in running economy (Figure 3; Table 3). In line with our finding, a previous study also reported that 8 weeks of combined continuous, interval and strength training among recreational runners significantly improved running economy and prolonged ground contact time 39 . Although most runners naturally select contact times that are close to their optimum value, one study found that runners often select slightly shorter contact times than optimal 57 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Among the spatiotemporal metrics, only increases in contact time were significantly associated with improvements in running economy (Figure 3; Table 3). In line with our finding, a previous study also reported that 8 weeks of combined continuous, interval and strength training among recreational runners significantly improved running economy and prolonged ground contact time 39 . Although most runners naturally select contact times that are close to their optimum value, one study found that runners often select slightly shorter contact times than optimal 57 .…”
Section: Discussionsupporting
confidence: 90%
“…The average improvements in running economy across all speeds were 6.1% and 7.7% for the control, and intervention groups, respectively. These changes are comparable to reductions found in previous studies were runners performed continuous running training without specific feedback on running technique 39–42 . Such improvements are larger than the between‐day typical error of ~2.5%, (range: 0.8%–3.3%) 43–45 and smallest worthwhile change of ~2.5% 43 reported for running economy in other studies and may therefore be considered clinically relevant.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, this remains a topic that needs further investigation to better understand the main mechanistic–energetic needs and, consequently, make meaningful methodological choices. Currently, there are numerous existing studies evaluating MP and energy expenditure, utilizing global positioning systems (GPS) and inertial measurement units (IMU) [ 24 , 32 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], but there is a complete absence of studies calculating these parameters from EMG technology. Analyzing submaximal and maximal sprint behavior with the aim of determining the MP and EC calculated by EMG and the EMG and force relationship could help clarify actual metabolic and neuromuscular engagement during linear running actions.…”
Section: Introductionmentioning
confidence: 99%